Avaliação do efeito de parâmetros microestruturais e de processo de impregnação de fluidos em colmos de bambusa vulgaris. - Júnior., Antônio da Silva Sobrinho (2010)
The interest of the use of Bamboo in the field of construction is growing around the world. This can be attributable to its good engineering properties as well as the fact that it comes from a renewable source. In the North-eastern, Bambusa vulgaris is the most common type. The aim of the research is to evaluate the parameters of impregnation of the bamboo with diverse fluids aiming at to the improvement of the mechanical properties and durability. In this way, it was necessary to evaluate the microstructure of the bamboo, so that the possibility of impregnation of these fluids can be observed. Some treatments of sample preparation had been tested for one better characterization of the porous structure of the bamboo through optic microscopy, having been chosen the attack for a FAA solution (4% of formaldehyde, 5% of acetic acid ascetic, 50% of ethylic alcohol). The constituents of the bamboo (parenchyma, fibers and vases) has been quantified and analyzed through a tool of recognition of images of optic microscopy. Of general form the mature bamboo presented 51.45% of parenchyma, 38.75% of fibres and 9.73% of vases. Already the young presented 57.64% of parenchyma, 33.55% of fibres and 8.81% of vases. The absorption of the culms was also evaluated by means of change in mass with time. The bamboo absorption capacity was assessed for different fluids along the time. The order of magnitude of the absorption is of 5 the 10%, independently of the used fluid. The absorption of the bamboo varied with the specific mass and viscosity of fluids. The pH of the young and a mature bamboo was determined, varying enters 5,72 the 6,61. Two machine of fluid impregnation was projected based in the Boucherie method, one for resin and to another one for the other fluid. Some parameters in the process of fluid impregnation had been studied in the bamboo, that is the following ones: viscosity and density of the fluid (distilled water, oil 20W and oil 40W), pressure of impregnation, time of harvesting of the bamboo (immediatly after harvesting and 7 days after harvesting), type of drying (greenhouse 50oC and to the outdoors) and geometric properties of the bamboo (initial and final mass, initial and final specific mass, volum, external, internal diameter and thickness of the wall). The variable of reply of the impregnation assay had been: time of fist drop, outflow and time to cross 20 g of fluid. An analysis was made statistics, where if it observed which independent variable had influenced significantly in the reply variable. It was observed that it is possible to impregnate fluid of diverse viscosities, mainly had the porous structure of the bamboo that is around 10%. The use of the machine if showed beneficial for this the process, therefore the pressure introduction also provoked a fast impregnation and a good development of flow. After the evaluation of the microstructural parameters and impregnation, the bamboos had been impregnated with a resin and evaluated some mechanical properties. The bamboos impregnated with resin had a bigger compressive strength, modulus of elasticity and a bigger durability of what the bamboos without treatment.